Seismic analysis and design of multilevel car parking using ETABS. (2022) - Kavitha, R.; Sundarraja, M.C.; Ram Vivekananthan, M.; Vinodhini, C.; Thiruvishnu, P.; Deepan, P.
Abstract: The main aim of this paper is to prepare the structural system, Seismic Analysis and design for Multi-level car parking using ETABS software. The Multilevel car parking consists of Ground + 6 floors. Type of foundation has been decided as pile foundation with pile cap. Multilevel car parking was designed for dead loads, live loads, wind and seismic loads. RC structure is analyzed by using the ETABS 2016 Integrated building design software. The superstructure is modeled by frame elements elements as appropriate. Beams and columns are modeled as frame elements, conventional slab is considered as membrane element. The floor slab has been modelled as a diaphragm at each floor levels to resist the lateral forces. Seismic zones are considered in the analysis, and behaviour is evaluated using moment resisting frame with a response reduction factor of 5. Loads and its combinations are considered for design as per codal provisions IS 456:2000 and IS 1893. The dimensions of the beams and columns are safe in the software. Crack width and deflection of beams are within permitted limits.